2003
DOI: 10.1074/jbc.m302333200
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Role for Phospholipase Cγ2 in Platelet Glycoprotein Ibα Calcium Flux and Cytoskeletal Reorganization

Abstract: Interaction of the platelet GPIb-V-IX complex with surface immobilized von Willebrand factor (vWf) is required for the capture of circulating platelets and their ensuing activation. In previous work, it was found that GPIb/vWf-mediated platelet adhesion triggers Ca 2؉ release from intracellular stores, leading to cytoskeletal reorganization and filopodia extension. Despite the potential functional importance of GPIb-induced cytoskeletal changes, the signaling mechanisms regulating this process have remained il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
105
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 41 publications
13
105
0
Order By: Relevance
“…4) was also suggested by other studies using an inhibitor of PI-PLC activity (U73122) or platelets deficient in the PLCγ2 isoform (Inoue et al, 2003;Mangin et al, 2003;Nakamura et al, 2001;Wonerow et al, 2003). The resulting cell phenotype was similar to that observed for deficiency in Src kinases in both cases, although it was more pronounced with U73122 than with disruption of PLCγ2 (Mangin et al, 2003;Wonerow et al, 2003).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…4) was also suggested by other studies using an inhibitor of PI-PLC activity (U73122) or platelets deficient in the PLCγ2 isoform (Inoue et al, 2003;Mangin et al, 2003;Nakamura et al, 2001;Wonerow et al, 2003). The resulting cell phenotype was similar to that observed for deficiency in Src kinases in both cases, although it was more pronounced with U73122 than with disruption of PLCγ2 (Mangin et al, 2003;Wonerow et al, 2003).…”
Section: Discussionsupporting
confidence: 71%
“…The inhibition of Src kinase activity in platelets also resulted in reduced cell spreading and loss of PLCγ2 phosphorylation following the engagement of von Willebrand factor or α2β1 and αIIbβ3 integrins (Inoue et al, 2003;Mangin et al, 2003;Wonerow et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…PLCc2-deficient murine platelets adhere to, but spread poorly on, immobilized VWF Adhesive interactions between human GPIb (huGPIb) and huVWF can be examined under static conditions by ''activating'' VWF immobilized on glass or plastic surfaces with conformational modifiers such as ristocetin or botrocetin. Previous studies [16,21] have shown that botrocetin is also able to support the binding of huVWF to murine platelets, resulting in shape change and aggregation. As shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Consistent with this notion, we found that pharmacological inhibition of total PLC activity by U73122, a PLC antagonist [24] while not affecting stable adhesion, completely abolished thrombus formation by human platelets on VWF (data not shown). Since PLCb isoforms do not appear to be involved in GPIb-mediated platelet activation [16], it is likely that PLCc1, though expressed at much lower levels than is PLCc2 [12], may compensate for the absence of PLCc2 in supporting thrombus formation on VWF. In fact, PLCc1 has recently been shown to function downstream of GPVI following platelet exposure to collagen [12].…”
Section: Resultsmentioning
confidence: 99%
“…2,8 Similarly, shear stress-independent, adhesiondependent GPIb-induced activation of ␣IIb␤3 apparently requires mobilization of internal stores but not Ca 2ϩ influx, ADP, or TxA2. 8,9 Despite these differences, GPIb-mediated signaling has been found to be PI3K 8,[10][11][12][13][14] and PLC␥2 dependent [14][15][16] in every system tested for these requirements. Because of the functional relationships between PI3K and Bruton tyrosine kinase (Btk), [17][18][19] Btk and PLC␥2 [20][21][22][23] activation, and the documented role of Btk in collagen-induced signaling in platelets, 19,24 we investigated the role(s) of Btk in TxA2 production induced by signaling elicited by bt/VWF/GPIb-mediated agglutination.…”
Section: Introductionmentioning
confidence: 99%